GENERATIVE ARTIFICIAL INTELLIGENCE AS AN INNOVATION IN EDUCATIONAL TECHNOLOGY: IMPLICATIONS FOR DIGITAL LEARNING AND TWENTY-FIRST-CENTURY COMPETENCIES - Edi Fitriana Afriza; Imelda Imelda; Teguh Arie Sandy; Muhammad Redo; Wayan Haarits Setiawan; Yohanes Payong; Muhammad Fillah Kurniawan (Universitas Labuhanbatu, 2026)
Purpose – This paper aims to analyze Generative Artificial Intelligence (GenAI) as an innovation in educational technology and examine its implications for digital learning and twenty-first-century competencies, particularly within the Indonesian context. Methodology – The study employs an integrative literature review method with a conceptual analysis approach. The literature sample comprises relevant international journal articles, official institutional reports, and theoretical frameworks (TPACK, SAMR, TAM, UTAUT, and ADDIE) published between 2020 and 2026. Data analysis followed a systematic four-stage procedure: identifying key concepts, grouping findings by thematic focus, analyzing through educational technology theories, and synthesizing the results into a critical narrative and tabular mapping.Findings – Results indicate that while GenAI accelerates learning resource production, enriches feedback, and supports adaptive learning, its pedagogical value is realized only when embedded within deliberate instructional design. Unregulated use presents significant risks, including information hallucination, algorithmic bias, data privacy violations, academic dishonesty, and unequal digital access.Contribution – This study contributes a comprehensive, theory-grounded GenAI integration model. It provides actionable frameworks for positioning educators as pedagogical guides, students as critical learning agents, and institutions as managers of responsible AI governance, offering vital policy and practical guidelines for advancing equitable, ethical, and effective digital education in Indonesia.